Current Construct Options for Revision of Large Acetabular Defects: A Systematic Review. Issue 11 (8th November 2016) - Baauw, Marieke; van Hooff, Miranda L.; Spruit, Maarten
Abstract : Background: Many treatment options are available for the revision of large acetabular defects. Debate continues as to which technique is most effective. Methods: A systematic review was performed according to the Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines to evaluate the effectiveness of interventions for large acetabular defects. Quality assessment was performed next with use of 8 items of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist for reports of observational studies. Large acetabular defects were defined as American Academy of Orthopaedic Surgeons (AAOS) type III or IV or Paprosky type 3A or 3B. Outcomes included re-revision, radiographic loosening, complications, and clinical outcomes. Results: We found 7 different treatment options for large acetabular defects in 20 included studies: antiprotrusio cage (8 studies), Trabecular Metal (Zimmer) augment and shell (4 studies), bone impaction grafting with a metal mesh (2 studies), hemispherical implant with hook and flanges (2 studies), Trabecular Metal augment or structural allograft with cup (2 studies), cup-cage reconstruction (1 study), and custom-made triflange component (1 study). Conclusions: Trabecular Metal augments and shells gave the most promising results in terms of the re-revision rate and radiographic loosening. Reconstruction with an antiprotrusio cage was the most frequently reported technique, with good results in a physically low-demand elderly population. Bone impaction grafting seems not appropriate for pelvic discontinuity and prone to failure in patients with Paprosky type-3B defects. In those cases, a custom-made triflange implant or a cup-cage reconstruction might be the best alternative, but few reports of sufficient quality are available yet. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.